Fusion technology of neural networks and fuzzy systems: A chronicled progression from the laboratory to our daily lives - Takagi, Hideyuki (Zielona Góra: Uniwersytet Zielonogórski)
We chronicle the research on the fusion technology of neural networks and fuzzy systems (NN + FS), the models that have been proposed from this research, and the commercial products and industrial systems that have adopted these models. First, we review the NN+FS research activity during the early stages of their development in Japan, the US, and Europe.
Keywords: cooperative models; neural networks; fuzzy systems; genetic algorithms; real world applications; overview